Assessing Direct Medical Costs and Quality of Life In Elderly Patients Using High-Alert Medications at Wongsonegoro Hospital - Supadmi, Woro; Endang Darmawan; Rizky Budi Santoso; Sri Sulistyorini (Media Farmasi: Jurnal Ilmu Farmasi, 2024)
High Alert Medications (HAM) are drugs that pose a significant risk of causing harm to patients if used incorrectly. This study aimed to evaluate the direct medical costs and quality of life of elderly patients aged 60 years and above using HAM at Wongsonegoro Hospital. An observational prospective cohort study design was employed, utilizing both secondary and primary data collection methods. Secondary data included patient demographics, medication usage, and direct medical costs obtained from hospital records and the finance department. Primary data on quality of life were gathered using the European Quality of Life 5 Dimensions (EQ-5D-5L) questionnaire. A total of 25 elderly patients were identified as users of HAM, with a gender distribution of 48% male and 52% female; 64% of these patients were aged between 60 and 70 years. The most prevalent medical condition among participants was diabetes mellitus, affecting 44% of one group and 32% of another. Sodium Chloride (NaCl) 500 mL infusion at a concentration of 3% was the most frequently administered medication (27.5%). The average direct medical cost for elderly patients using HAM was IDR 4,255,050. Additionally, the quality of life assessment revealed that 20% of patients experienced significant challenges in self-care activities. These findings highlight the impact of HAM on healthcare costs and quality of life among elderly patients, emphasizing the need for careful monitoring and management strategies to mitigate risks associated with high-alert medications.